9(x+6)+5=59

Simple and best practice solution for 9(x+6)+5=59 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9(x+6)+5=59 equation:


Simplifying
9(x + 6) + 5 = 59

Reorder the terms:
9(6 + x) + 5 = 59
(6 * 9 + x * 9) + 5 = 59
(54 + 9x) + 5 = 59

Reorder the terms:
54 + 5 + 9x = 59

Combine like terms: 54 + 5 = 59
59 + 9x = 59

Add '-59' to each side of the equation.
59 + -59 + 9x = 59 + -59

Combine like terms: 59 + -59 = 0
0 + 9x = 59 + -59
9x = 59 + -59

Combine like terms: 59 + -59 = 0
9x = 0

Solving
9x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Divide each side by '9'.
x = 0

Simplifying
x = 0

See similar equations:

| -533-(-276)= | | -2(-6k-5)=-15+7k | | -x+3+11x=-3+4x+48 | | .5x+.05x=256 | | 4(5k-5)+19=-9+2(3k-8) | | 13+3(2x-5)=1-2(3-6x) | | 3c-1c+40=34 | | 4/3+2=6 | | x+2x+13=70 | | 7.5-(-2.5)= | | a(c-2)+3(c-2)= | | 92=-8+25m | | x+.05x=23.63 | | -(5+2x)=2(3+4x) | | 5t-14=8t+4 | | 3(n-5)=9-n | | 2x+4=-1(7x+6) | | 1(5+2x)=2(3+4x) | | 8y-8=64 | | 5y/6-23=7 | | 350x23/20x7/25 | | 5t-1=24 | | 3.0-(-5.3)= | | 5+X+X=1+4X | | x+.06x=22.64 | | 4x+6+x=3+2x-3 | | x+4(x+1)=47 | | 2t-5=29 | | 2(3n-4)=-26+3n | | 2x+61=3x-8 | | -11=4u+5 | | 5y-16=49 |

Equations solver categories